Mewujudkan Doktrin Duty of Care dan Business Judgment Rule dalam Hukum Perseroan Terbatas di Indonesia - Wihelmus Jemarut (Jurnal Hukum Agama Hindu Widya Kerta, 2022)
The main question that explained in this research is, “how is the implementation of the authority of the Board of Directors in the frame of the doctrine “duty of care” and “business judgment rule”? The research method used in this writing is normative research method with two approaches: doctrinal and legislation. The conclusion that the researcher found from the research in this writing is the “duty of care” doctrine is the basic concept to implement the doctrine “business judgment rule”. The board of director can get the legal protection based on the theory “business judgment rule” if the doctrine duty of care is fulfilled. The researcher suggests that the legislation of Limited Liability Company (Ltd.) need to make the clear and assertive provision about the standard of circumspection and the standard of good intention from the Board of Director in managing the company.